Cultures colliding: American missionaries, Chinese resistance, and the rise of modern institutions in China - Haddad, John R. (Temple University Press, 2023)
"This book tells the history of how and why American missionaries started building schools, colleges, medical schools, hospitals, and YMCA chapters in China before 1900"--